Redefining outpatient dengue management 18 years on: lessons from a national tertiary centre - Jinghao Nicholas Ngiam; Matthew Chung Yi Koh; Brenda Mae Alferez Salada; Dale Fisher; Sophia Archuleta; Jolene Ee Ling Oon (Travel Medicine and Infectious Disease, 2025)
Background: Dengue fever places a substantial burden on healthcare systems in endemic areas. Traditional inpatient management places strain on hospital capacity during seasonal surges. This study evaluates an expanded nurse-led Dengue Outpatient Management (DOM) program at a tertiary centre in Singapore. Methods: A prospective observational study was conducted from January 2023 to August 2024. DOM inclusion criteria were broadened to include older adults and patients with comorbidities, if clinically stable. Patients received physician evaluation, a nurse-led symptom-based assessment and vital signs monitoring. Results: There were 167 patients managed in DOM in the study period. The model saved an average of 3.3 bed-days per patient, amounting to approximately 231 bed-days saved in 2023. Conclusion: This expanded nurse-led outpatient dengue management model demonstrates safety, feasibility, and resource efficiency. With structured patient selection and monitoring protocols, DOM significantly reduces hospital bed occupancy while offering a scalable solution for dengue-endemic regions.